Retinoblastoma in Chinese children aged five to fourteen years - Chang, Ying; Jonas, Jost B. (Ophthalmologica, 2015)
Objective: To assess the characteristics of retinoblastomas enucleated from Chinese children aged 5-14 years. Methods: This retrospective hospital-based study included all eyes with retinoblastomas consecutively enucleated in the Beijing Tongren Hospital between August 2003 and July 2013. Results: Out of 1,205 patients, 47 (3.9%) were 5 years or older. All tumors in this age group occurred unilaterally, the patients had a negative family history, and the tumors were detected at an age of 6.9 ± 1.8 years (range: 5-14). The main clinical features at the time of examining the as yet untreated children aged 5-7 years (n = 30) or >7-14 years (n = 10) were leukocoria, strabismus, pseudohypopyon, hypertension, vitreous seeds (‘snowballs'), and calcifications. In 12 patients (26%), the retinoblastoma had not initially been diagnosed as a tumor. Histopathology revealed tumor invasion into nonretinal tissue in 19 eyes (40%). Therapy included enucleation only (n = 22; 47%), adjuvant systemic chemotherapy (n = 24; 51%), and additional orbital exenteration (n = 1). After a mean follow-up of 3.0 ± 2.1 years (range: 0.2-9.8), which was done for 40 children, none of these children showed a tumor recurrence. Conclusions: Of the children undergoing enucleation for retinoblastoma in Beijing, 3.9% were aged 5 years or more. As in Western countries, the tumor occurrence was unilateral, their family history was negative, and the survival rate was relatively high in these children. In 1 out of 4 children, the tumor had initially been misdiagnosed due to a masquerade syndrome. Retinoblastoma should be considered in the differential diagnosis of any unclear intraocular situation in children.